Seeking new acne treatment from natural products, devices and synthetic drug discovery. Issue 1 (1st January 2017) - Yang, Ji Hoon; Yoon, Ji Young; Kwon, Hyuck Hoon; Min, Seonguk; Moon, Jungyoon; Suh, Dae Hun
ABSTRACT: Despite lots of research on the pathogenesis of acne, the development of new therapeutic agents is still stagnant. Conventional agents which target multiple pathological processes have some serious side effects and this makes seeking new treatment options important for treating acne. As new therapeutic options, researchers are focusing on natural products, synthetic drugs and devices. From natural products, epigallocatechin-3 gallate, lupeol, cannabidiol and Lactobacillus fermented Chamaecyperis obtusa were reported to be possible candidates for novel drugs, targeting multiple pathogenic factors. Synthetic anti- P.acnes agent, nitric oxide nanoparticles and α-mangostin nanoparticles are shown to be effective in acne treatment. Device or procedural methods such as fractional microneedling radiofrequency, cryolysis, photothermolysis and daylight photodynamic therapy have potential as new treatment options for acne. Further large clinical trials comparing these new treatments with existing agents will be necessary in the future.